Internal Entropy Production as a Lyapunov Function for Thermal Equilibrium in Irreversible Multiphase Systems. Issue 18 (2022) - Romo-Hernandez, Aarón; Hudon, Nicolas; Ydstie, B. Erik; Dochain, Denis
Abstract: Thermodynamics has served as a framework to establish physics-based criteria for the stabilization, control and optimization of process systems. In this article, we establish conditions for the internal entropy production rate to characterize the stability properties of thermal equilibrium in irreversible multiphase systems. In particular, in Theorem 1, we show how, as a multiphase system evolves towards equilibrium, internal entropy production decreases monotonically in time for a particular class of multiphase systems. Being positive semi-definite and having a semi-negative definite time derivative, internal entropy production is thus a Lyapunov function that characterizes the stability of thermal equilibrium in multiphase irreversible systems.